Stomach and duodenum dose–volume constraints for locally advanced pancreatic cancer patients treated in 15 fractions in combination with chemotherapy - Broggi, Sara; Passoni, Paolo; Tiberio, Paolo; Cicchetti, Alessandro; Cattaneo, Giovanni Mauro; Longobardi, Barbara; Mori, Martina; Reni, Michele; Slim, Najla; Del Vecchio, Antonella; Di Muzio, Nadia G.; Fiorino, Claudio (Frontiers in Oncology, 2023)
Purpose: To assess dosimetry predictors of gastric and duodenal toxicities for locally advanced pancreatic cancer (LAPC) patients treated with chemo-radiotherapy in 15 fractions. Methods: Data of 204 LAPC patients treated with induction+ concurrent chemotherapy and radiotherapy (44.25Gy in 15 fractions) were available. Forty-three patients received a simultaneous integrated boost to 48-58Gy. Gastric/duodenal CTCAEv5 Grade ≥2 toxicities were analyzed. Absolute/% duodenum and stomach DVHs of patients with/without toxicities were compared: the most predictive DVH points were identified and their association with toxicity tested in univariate and multivariate logistic regressions together with near-maximum dose (D0.03) and selected clinical variables. Results: Toxicity occurred in 18 patients: 3 duodenal (ulcer, duodenitis) and 10 gastric (ulcer, stomatitis); 5/18 experienced both. At univariate analysis, V44cc (duodenum: p=0.02, OR=1.07; stomach: p=0.01, OR=1.12) and D0.03 (p=0.07, OR=1.19; p=0.008, OR=1.12) were found the most predictive parameters. Stomach/duodenum V44 and stomach D0.03 were confirmed at multivariate analysis and found to be sufficiently robust at internal, bootstrap-based, validation; the results regarding duodenum D0.03 were less robust. None clinical variables neither %DVH were significantly associated with toxicity. The best duodenum cut-off values were V44<9.1cc (and D0.03<47.6Gy); concerning stomach, they were V44<2cc and D0.03 <45Gy. The identified predictors showed high negative predictive value (>94%). Conclusion: In a large cohort treated with hypofractionated radiotherapy for LAPC, the risk of duodenal/gastric toxicities was associated to duodenum/ stomach DVH. Constraining duodenum V44<9.1cc, stomach V44<2cc, stomach D0.03<45Gy should keep the toxicity rate around or below 5%. The association with duodenum D0.03 was not sufficiently robust due to the limited number of events, although results suggest that a limit of 45-46Gy should be safe.